Yield and quality responses of Aragonez grapevines under deficit irrigation and different soil management practices in a Mediterranean climate - Tomaz, Alexandra (2015)
In Mediterranean-type climates, increased irrigation efficiency is a key goal for viticulture, as it is for fruit production in general. The objective of the present study was to determine the responses of yield, berry composition, and wine quality to various degrees of irrigation supply and different soil management practices in a vineyard. Data were collected during two years from ‘Aragonez’ grapevines (Vitis vinifera L. syn. ‘Tempranillo’). The experimental site was located in a private vineyard in the Baixo Alentejo, southern Portugal. The vineyard is grown on vertisols, with drip irrigation. In the 4 ha area under study, a cover crop in the interrow was sown in half the plots, with the permanent resident vegetation maintained in the other half. The irrigation treatments were: high water availability (200 mm annual irrigation supply); moderate water availability (150 mm annual irrigation supply); deficit irrigation (100 mm annual irrigation supply); ultra-deficit irrigation (50 mm annual irrigation supply); rainfed. The deficit and ultra-deficit irrigation treatments were conducted in accordance with the Regulate Deficit Irrigation (RDI) strategy. The vine's vegetative growth and yield responses influenced by irrigation in both years were: pruning weight, yield, and cluster weight. The quality responses were different in the two years of study: the grape composition parameters that showed significant differences were few and different each year; in wine composition, only in 2008 was the effect of irrigation on titratable acidity proven. Vegetative growth and yield were lower in the presence of the sown cover crop. The composition of grapes and wine was mostly affected by the surface cover in 2008, with the best performance for the phenolic compounds corresponding to plants growing on plots with permanent sown cover crop. The phenolic component in grapes benefited from the presence of the sown cover crop and the successful application of the RDI strategy.